Short‐Term Carbohydrate Restriction Impairs Bone Formation at Rest and During Prolonged Exercise to a Greater Degree than Low Energy Availability. (10th August 2022) - Fensham, Nikita C.; Heikura, Ida A.; McKay, Alannah K.A.; Tee, Nicolin; Ackerman, Kathryn E.; Burke, Louise M.
ABSTRACT: Bone stress injuries are common in athletes, resulting in time lost from training and competition. Diets that are low in energy availability have been associated with increased circulating bone resorption and reduced bone formation markers, particularly in response to prolonged exercise. However, studies have not separated the effects of low energy availability per se from the associated reduction in carbohydrate availability. The current study aimed to compare the effects of these two restricted states directly. In a parallel group design, 28 elite racewalkers completed two 6‐day phases. In the Baseline phase, all athletes adhered to a high carbohydrate/high energy availability diet (CON). During the Adaptation phase, athletes were allocated to one of three dietary groups: CON, low carbohydrate/high fat with high energy availability (LCHF), or low energy availability (LEA). At the end of each phase, a 25‐km racewalk was completed, with venous blood taken fasted, pre‐exercise, and 0, 1, 3 hours postexercise to measure carboxyterminal telopeptide (CTX), procollagen‐1 N‐terminal peptide (P1NP), and osteocalcin (carboxylated, gla‐OC; undercarboxylated, glu‐OC). Following Adaptation, LCHF showed decreased fasted P1NP (~26%; p  < 0.0001, d  = 3.6), gla‐OC (~22%; p  = 0.01, d  = 1.8), and glu‐OC (~41%; p  = 0.004, d  = 2.1), which were all significantly different from CON ( p  < 0.01), whereas LEA demonstrated significant, but smaller, reductions in fasted P1NP (~14%; p  = 0.02, d  = 1.7) and glu‐OC (~24%; p  = 0.049, d  = 1.4). Both LCHF ( p  = 0.008, d  = 1.9) and LEA ( p  = 0.01, d  = 1.7) had significantly higher CTX pre‐exercise to 3 hours post‐exercise but only LCHF showed lower P1NP concentrations ( p  < 0.0001, d  = 3.2). All markers remained unchanged from Baseline in CON. Short‐term carbohydrate restriction appears to result in reduced bone formation markers at rest and during exercise with further exercise‐related increases in a marker of bone resorption. Bone formation markers during exercise seem to be maintained with LEA although resorption increased. In contrast, nutritional support with adequate energy and carbohydrate appears to reduce unfavorable bone turnover responses to exercise in elite endurance athletes. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).